Railroads and American political development : infrastructure, federalism, and state building - Callen, Zachary (University Press of Kansas, 2016)
"Whether the federal government could play any role in the development of infrastructure was a controversial issue in the early republic. Spending on roads and harbors was not one of the enumerated powers; therefore many argued such projects were left to the states. Demand for better transportation increased as the country grew, which put pressure on the federal government to become involved in the development of national infrastructure. Roads and harbors were the first projects the federal government supported. As railroads developed they also became objects of federal interest. This book tells a story about the development of the American state through the demand for support of railroads. Growing demand for national rail networks combined with the failure of many state initiatives put pressure on the federal government to act. This is a story of the development of the state from ground up"--